Correction to "A description of four new species of Clavicornaltica Scherer from Continental Asia" - Konstantinov, Alexander S.; Duckett, Catherine N. (Zootaxa, 2005)
We recently published descriptions of four species of Clavicornaltica Scherer from Continental Asia (Konstantinov and Duckett 2005). These species were compared to known species including Clavicornaltica australis Konstantinov. Due to an unfortunate event the figure showing the male genitalia of C. australis was omitted. This figure shown below (Fig. 1) is cited in the discussion on page 62 as figure 32.